Design And Analysis Of Cansat Module For Education - Johari, Nur Juliana Ahmad (Universiti Sains Malaysia, 2019)
Design and Analysis of CanSat Module for Education is a project focuses on the development of STEM education space-based technology tools for educational purpose initiated by the USM Space System Lab (USSL). A research on CanSat Kit for Education (CakEd) is a way of teaching and learning fundamental of space education to secondary school students using a CanSat or can satellite in soda can size that can be launched from a rocket, drone or a balloon. The system of the satellite including a control system, telemetry system, power system and payload system. This project focuses on integrating of learning and teaching module for CanSat which consist of hardware, software and web based learning system. Improvement for the hardware requires a new structural design of CanSat using design software Solidworks for the latest electronic module packaging. A GUI system for CanSat user with a web based learning system is developed to provide a systematic data collection system from telemetry system of CanSat. The end process of integrating elements of CanSat by fabricating and packaging of CakEd. This study also investigates the effectiveness of CanSat teaching and learning module through outreach program. Improvement can be done afterwards based on the feedback and recommendation from user. At the end of the study, a complete CanSat Kit for Education produced and ready to be commercially used.